Answer:
She knew that they were destined to be together. She even smelt like mangos. She also had a pastor come to her house and help her get married. It is actually not that difficult to figure out.
Step-by-step explanation:
Brainliest?
Answer:
= 1 7/8
Step-by-step explanation:
Since f(x) is a polynomial with 3rd degree, then it will have 3 roots (zeroes)
One of them is real and the other two are complex conjugate roots
Since the real root is 4, then
x = 4
Since the complex root is (1 - i), then
The other root will be the conjugate of it (1 + i)
x = (1 - i)
x = (1 + i)
To find f(x) we will multiply the three factors of it
We can get the factors from the zeroes
![x=4](https://tex.z-dn.net/?f=x%3D4)
Subtract 4 from both sides
![\begin{gathered} x-4=4-4 \\ x-4=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x-4%3D4-4%20%5C%5C%20x-4%3D0%20%5Cend%7Bgathered%7D)
The first factor is (x - 4)
![\begin{gathered} x=1-i \\ x-(1-i)=(1-i)-(1-i) \\ x-1+i=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%3D1-i%20%5C%5C%20x-%281-i%29%3D%281-i%29-%281-i%29%20%5C%5C%20x-1%2Bi%3D0%20%5Cend%7Bgathered%7D)
The second factor is (x - 1 + i)
The third factor is (x - 1 - i)
![f(x)=(x-4)(x-1+i)(x-1-i)](https://tex.z-dn.net/?f=f%28x%29%3D%28x-4%29%28x-1%2Bi%29%28x-1-i%29)
We will multiply them to find f(x)
![\begin{gathered} (x-1+i)(x-1-i)= \\ x^2-x-ix-x+1+i+ix-i-(i^2)= \\ x^2-2x+1-(-1)= \\ x^2-2x+1+1= \\ x^2-2x+2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28x-1%2Bi%29%28x-1-i%29%3D%20%5C%5C%20x%5E2-x-ix-x%2B1%2Bi%2Bix-i-%28i%5E2%29%3D%20%5C%5C%20x%5E2-2x%2B1-%28-1%29%3D%20%5C%5C%20x%5E2-2x%2B1%2B1%3D%20%5C%5C%20x%5E2-2x%2B2%20%5Cend%7Bgathered%7D)
Multiply it by (x - 4)
![\begin{gathered} f(x)=(x-4)(x^2-2x+2) \\ f(x)=x^3-2x^2+2x-4x^2+8x-8 \\ f(x)=x^3-6x^2+10x-8 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D%28x-4%29%28x%5E2-2x%2B2%29%20%5C%5C%20f%28x%29%3Dx%5E3-2x%5E2%2B2x-4x%5E2%2B8x-8%20%5C%5C%20f%28x%29%3Dx%5E3-6x%5E2%2B10x-8%20%5Cend%7Bgathered%7D)
The answer is
For compound interest, the formula is given below:
Amount = ![P(1+\frac{r}{100} )^{n}](https://tex.z-dn.net/?f=P%281%2B%5Cfrac%7Br%7D%7B100%7D%20%29%5E%7Bn%7D)
Here, P = 18,800
n = 2
r = 13/100
So, Amount = ![18,800(1+\frac{13}{100} )^{2}](https://tex.z-dn.net/?f=18%2C800%281%2B%5Cfrac%7B13%7D%7B100%7D%20%29%5E%7B2%7D)
![18,800(1.13)^{2}](https://tex.z-dn.net/?f=18%2C800%281.13%29%5E%7B2%7D)
= 18,800 × 1.2769
= 24005.72
Compound Interest = Amount - Principal
Compound Interest = 24005.72 - 18800
= 5205.72
Hence, the compound interest for Rs.18,800, calculated for 2 years at 13% rate of interest compounded annually is Rs.5205.72.
Answer:
The second option
Step-by-step explanation:
The answer is negative (The blue line is below the x axis)
for all x values between -2 and -6 is a true statement
The first option is incorrect because the function is negative between -4 and -2.
The third option is incorrect because the function is negative between -3 and -2.
The forth option is incorrect because the function is positive for x < -6.